Bidirectional coordinating dispatch of large-scale V2G in a future smart grid using complementarity optimization. (June 2015) - Bai, Xiaoqing; Qiao, Wei; Wei, Hua; Huang, Feng; Chen, Yinjie
Highlights: We propose an optimization model for bidirectional coordinating dispatch of PEVs. The proposed model is based on a hierarchically coordinated operation framework. The proposed model is solved by a complementarity modern interior point algorithm. Simulation results show that the proposed model has good convergence. Optimally coordinating the dispatch of charge and discharge of PEVs is beneficial. Abstract: This paper proposes a nonlinear complementarity optimization model for bidirectional coordinating dispatch of large-scale plug-in electric vehicles (PEVs) in a future power grid based on a hierarchically coordinated operation framework. The proposed model focuses on the top-level Independent System Operator's operation module of the framework, in which the PEV fleets are considered as a type of dispatchable demand response and energy storage resource. Using a relaxation method for the complementarity constraints, a complementarity modern interior point algorithm is developed for solving the proposed model. Computer simulations are performed for a power grid with 10 generators and three PEV fleets. Results show that the proposed model is better than the traditional quadratic programing models and the proposed algorithm has good convergence. Optimally coordinating the dispatch of charge and discharge of PEVs are beneficial to reducing the generation cost and CO2 emission while satisfying the transportation requirement of the PEVs.